2021
DOI: 10.1039/d0ay01988g
|View full text |Cite
|
Sign up to set email alerts
|

A simple fluorescence-based lateral flow test platform for rapid influenza B virus screening

Abstract: A simple and rapid fluorescence-based screening platform for influenza B virus using a one-step Cy5-SiNPs–mAb bioconjugation on lateral flow-based technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…SiO 2 NPs are also suitable for loading a variety of substances ranging from small quantum dots to large enzymes. 365 For example, pomegranate-shaped SiO 2 NPs (thickness: 5 nm) show high uptake of quantum dots and they can be functionalized with antibodies for rabies lyssavirus detection. 366 Timely detection of the virus is critical since rabies is almost always fatal after the onset of its symptoms such as hydrophobia, nausea, unconsciousness.…”
Section: Inorganic Nanomaterials In Virus Sensing and Trackingmentioning
confidence: 99%
“…SiO 2 NPs are also suitable for loading a variety of substances ranging from small quantum dots to large enzymes. 365 For example, pomegranate-shaped SiO 2 NPs (thickness: 5 nm) show high uptake of quantum dots and they can be functionalized with antibodies for rabies lyssavirus detection. 366 Timely detection of the virus is critical since rabies is almost always fatal after the onset of its symptoms such as hydrophobia, nausea, unconsciousness.…”
Section: Inorganic Nanomaterials In Virus Sensing and Trackingmentioning
confidence: 99%
“…Wiriyachaiporn et al addressed the influenza B virus nucleoprotein with a fluorescence‐based lateral flow test. The protein is first captured with specific antibodies and then detection is enabled using silica nanoparticles coupled with Cy5 and specific antibodies [106]. Takemura et al proposed another fluorescence‐based detection scheme for the NS1 protein of the Zika virus.…”
Section: Virus Detectionmentioning
confidence: 99%
“…This LFA was fabricated into a 5G-enabled device to realize the real-time recording of patient data. Wiriyachaiporn et al reported a simple fluorescent-based LFA platform using Cy5-dye-doped silica nanomaterials as fluorescent labels for rapid influenza B virus screening [ 66 ]. This work suggested that the carboxyl modification of silica nanomaterials could prevent the denaturation of biomolecules in harsh environments.…”
Section: Fluorescent Lfas Using Silica Nanomaterialsmentioning
confidence: 99%